2019
DOI: 10.1590/0102-33062018abb0272
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 concentration improves water use efficiency and growth of a widespread Cerrado tree species even under soil water deficit

Abstract: Changes in atmospheric CO 2 levels are accompanied by ecological interactions involving other environmental factors, such as drought, which can severely alter the water balance of plants, thereby influencing sap flow, gas exchange, and plant growth. The objective of this study was to evaluate the water use economy, leaf gas exchange, and growth of young plants of the species Lafoensia pacari subjected to high concentrations of atmospheric CO 2 ([CO 2 ]) and soil water deficit. Increased vapor pressure deficit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…In previous studies with cerrado species, Souza et al (2016) pointed out that woody plants growing under elevated [CO 2 ] and soil water deficit showed improved growth. Also, Souza et al (2019) showed an increase in water use efficiency in Lafoensia pacari juvelines under elevated [CO 2 ] and soil water deficit. Therefore, we expected that even with synergism between high [CO 2 ] and drought events, cerrado plants would be benefited in the future.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies with cerrado species, Souza et al (2016) pointed out that woody plants growing under elevated [CO 2 ] and soil water deficit showed improved growth. Also, Souza et al (2019) showed an increase in water use efficiency in Lafoensia pacari juvelines under elevated [CO 2 ] and soil water deficit. Therefore, we expected that even with synergism between high [CO 2 ] and drought events, cerrado plants would be benefited in the future.…”
Section: Discussionmentioning
confidence: 97%
“…3e), signifying that a reduction in water loss plays a more important role in increasing WUE. This may help delay the onset and reduce the degree of moisture stress (Wang et al 2012), in turn extending the length of the growing season in forest ecosystems (Souza et al 2019).…”
Section: Woody Plant Responses To Varying Eco 2 Concentrationsmentioning
confidence: 99%
“…Plants have different temperature domains that initially determine their geographic distribution [70] but with the progressive increase in air temperature, the temperature domains become displaced to colder regions, forcing plant species to move away from their current distribution [71,72]. The increase in temperature may cause several types of damage to plants in different stages of life, from germination to adulthood [73,74]. The temperature range considered optimal for photosynthesis in C3 plants is between 18°C and 30°C, while temperatures above 30°C are considered to be heating zones [70,75].…”
Section: Thermal Stress Triggers Morphological and Physiological Damamentioning
confidence: 99%